A self-assembly reproducible nanoplatform enables cancer phenotypic lethality in solid tumors. (February 2022) - Yang, Xi; Gao, Ling; Wang, Ning; Li, Yongjiang; Song, Linjiang; He, Tao; Zhang, Wenli; Yi, Cheng; He, Gu; Wu, Qinjie; Gong, Changyang
Graphical abstract: The self-assembly reproducible nanoplatform (SRNA) could efficiently silence MutT Homolog1 (MTH1) expression and accumulated oxidized deoxynucleoside triphosphates pool in cancer cells, leading to a therapeutic response in ovarian cancer. The SRNA for efficiency delivery of siMTH1 may provide a practical paradigm to induce cancer phenotypic lethality in solid tumors. Highlights: A self-assembly reproducible nanoplatform (SRNA) was designed. Cholesteryl-peptides have precise molecular weight and low variability. SRNA efficiently silence MTH1 and accumulated oxidized dNTPs in cancer cells. SRNA enables cancer phenotypic lethality by efficient delivery of MTH1 siRNA. Abstract: Cancer phenotypic lethality targets a nonessential enzyme in normal cells that is required for cancer survival, which can overcome the problem of the high degree of intra-tumor heterogeneity and be more widely applicable, irrespective of the cancer genotype. Altered redox regulation is a cancer phenotype and damages both the DNA and free deoxynucleoside triphosphates (dNTPs) pool. MutT Homolog1 (MTH1) plays a critical role in removing oxidized dNTPs, avoiding incorporation of these damaged bases. This study aimed to construct a self-assembly reproducible nanoplatform (SRNA) to actualize cancer phenotypic lethality in solid tumors by efficiently delivering of MTH1 siRNA (siMTH1). Compared with conventional polymer vectors, the synthesized cholesteryl-peptides had precise molecular weights, good biocompatibility and low variability. Thus, the cholesteryl-peptides were used to form a compact SRNA with siMTH1 and protect siMTH1 against degradation. The SRNA silenced MTH1 expression and accumulated oxidized dNTPs in cancer cells, leading to a therapeutic response in ovarian cancer. In summary, the SRNA for the efficient delivery of siMTH1 may provide a practical paradigm to induce cancer phenotypic lethality in solid tumors.